Malignant mesenchymal tumor with leiomyosarcoma, rhabdomyosarcoma, chondrosarcoma, and osteosarcoma differentiation: case report and literature review - Dai Ming-Shen; Wu Seng-Tang; Yu Cheng-Ping; Li Yao-Feng; Lee Herng-Sheng (BMC, 2011)
Abstract A case of malignant mesenchymoma of the bladder containing leiomyosarcoma, rhabdomyosarcoma, chondrosarcoma, osteosarcoma, and myxomatous components is described. The primary pedunculated tumor measuring 14 × 13 × 7 cm and weighing 343 g arose from the left trigone of the bladder and was treated by total cystectomy. The histogenesis of malignant mesenchymomas and their optimal management strategy and prognosis remain uncertain. Herein, we present the fifth case of malignant mesenchymoma of the urinary bladder to be reported in the literature, which presented five unrelated differentiated tissues more than did previously reported cases.